2008
DOI: 10.1002/cc.310
|View full text |Cite
|
Sign up to set email alerts
|

Community college governance: What matters and why?

Abstract: This chapter sets the stage for understanding the importance of governance in the community college.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The community college setting was chosen as an institutional type for a reason. Facing a period of leadership transition (Amey, Jessup-Anger, & Jessup-Anger, 2008;Wiessner & Sullivan, 2007) and an increasingly complex environment (Eddy, 2012), community colleges across the country have been actively engaged in developing shared leadership models over the past several decades. As Kezar (1998) observed, "A dramatic shift is taking place on community college campuses as their leaders move from Downloaded by [University of Nebraska, Lincoln] at 14:21 02 February 2015 traditional, hierarchical forms of leadership to participatory models" (p. 75).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The community college setting was chosen as an institutional type for a reason. Facing a period of leadership transition (Amey, Jessup-Anger, & Jessup-Anger, 2008;Wiessner & Sullivan, 2007) and an increasingly complex environment (Eddy, 2012), community colleges across the country have been actively engaged in developing shared leadership models over the past several decades. As Kezar (1998) observed, "A dramatic shift is taking place on community college campuses as their leaders move from Downloaded by [University of Nebraska, Lincoln] at 14:21 02 February 2015 traditional, hierarchical forms of leadership to participatory models" (p. 75).…”
Section: Methodsmentioning
confidence: 99%
“…As Kezar (1998) observed, "A dramatic shift is taking place on community college campuses as their leaders move from Downloaded by [University of Nebraska, Lincoln] at 14:21 02 February 2015 traditional, hierarchical forms of leadership to participatory models" (p. 75). Indeed, in the face of the complex challenges that community college leadership is facing with fewer experienced leaders to guide institutions, team-based leadership is increasingly found as a viable alternative as well as training grounds for midlevel leaders to develop leadership skills, attitudes, and perspectives (Amey et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The presidents reported that it often can be challenging for a leader to maintain progress toward transforming the college when new members join the board (Alsbury, 2003;Boggs & Smith, 1997;Brown, et al, 2001). In particular it is difficult when there is annual turnover of trustees (Amey, Jessup-Anger, & Jessup-Anger, 2008 They also commented on how difficult it is for a leader to help some new trustees, who have never been involved with a prominent organization like a community college governing board, to balance their perceptions of personal power and prestige in this new role with their responsibility for the college as a whole and its stakeholders (Davis, 2001).…”
Section: Correcting Misleading Informationmentioning
confidence: 99%
“…Rural community college presidents were increasingly asked to lead community initiatives. They then brought those community issues back to their colleges and found ways for the college as well as its faculty, staff, and students, to become more involved in overall community improvement (Amey, Jessup-Anger, & Jessup-Anger, 2008).…”
Section: Early Adoption Of Comprehensive Economic Development Strategiesmentioning
confidence: 99%
“…They did this out of necessity, to become better regional partners in improving economic conditions, but also to prove their usefulness as change agents (K. Pennington & Williams, 2004). Rural community college presidents were asked to lead community initiatives and then brought those community issues back to their colleges, finding ways for the college, as well as its faculty, staff, and students to get more involved in overall community improvement (Amey et al, 2008).…”
Section: Limiting Factorsmentioning
confidence: 99%